Strategi Tauke Kelapa Sawit dalam Mempertahankan Klien di Desa Pasir Emas Kecamatan Singingi Kabupaten Kuantan Singingi - Iirna Andriyanti; Yusmar Yusuf; Resdati Resdati (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
The condition of oil palm fruit in Pasir Emas village has decreased in quantity or commonly referred to as "trek", so this disturbs and even reduces half of the tauke's income. In addition, erratic price fluctuations, the number of sorting or factory pieces that reach 300 to 500 kilograms, as well as the large number of tauke expenses due to the rainy season and damaged road conditions and other expenses also affect the stability of capital and business continuity of the tauke, so that oil palm tauke needs a strategy to retain customers. The purpose of this research is to see the tauke's strategy in retaining customers in Pasir Emas Village. In this study, there are three strategies used, namely alternative livelihood strategies, tighter belt strategies and relationship strategies. The type of research used is descriptive qualitative with data collection techniques namely interviews, documentation and observation. The results show that the relationship strategy used by the tauke is to provide assistance and priority to customers, listen to complaints, be friendly and communicate well with customers, pay customers' fruit on time, weigh customers' fruit appropriately, and cooperate with other parties. The strategies used to tighten the belt are repairing road damage, selling fruit to the nearest factory, and saving money. The alternative livelihood strategy used by the Tauke is to have a second job.